ANALISIS MINAT PENGGUNAAN DIGITAL WALLET MAHASISWA DI KABUPATEN LABUHANBATU - Elvina Harahap; Pitriyani Pitriyani; Eva Fitria (Journal of Global Business and Management Review, 2022)
Digital wallets are included in electronic or digital payments that are widely used by the public in making online transactions. The purpose of this study was to analyze student interest in using digital wallets in Labuhanbatu Regency. This research method is descriptive qualitative. The sample in this study were students in tertiary institutions in Labuhanbatu Regency. Data collection techniques were carried out through in-depth interviews (In-depth Interview). Data analysis techniques are carried out by detecting student knowledge about student interest and using a digital wallet and student disinterest and not using a digital wallet. The results showed that the percentage of digital wallet users for male gender was 38 people (25.33%) and women were 112 people (74.67%). The percentage of interest in using a digital wallet is 68% which uses OVO, DANA, and Gopay. The reason for using a digital wallet is because online transactions are considered easy and convenient. Meanwhile, 32% of respondents answered that they were not interested and did not use a digital wallet because it is more convenient to use cash in making transactions.